1982
DOI: 10.1002/eji.1830120911
|View full text |Cite
|
Sign up to set email alerts
|

Intrastrain recurrent idiotypes among anti‐DNA antibodies of (NZB X NZW)F1 hybrid mice

Abstract: Immunization of NZB and A/J mice against an anti-DNA hybridoma antibody (F227) derived from (NZB x NZW)F1 (B/W) mice allowed the preparation of two anti-idiotypic antisera. These two reagents were shown to recognize different idiotopes of the F227 monoclonal antibody. NZB anti-idiotypic antibodies recognized non-ligand-modifiable idiotypic determinants. These idiotopes were private or present at undetectable level in BW mouse sera since it was found that only two of the 24 B/W mouse sera tested were recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Evidence has been presented elsewhere for the anti-Id specificity of the NZB and A/J mouse antisera prepared against F227 mAb (7). The data in Table 2 provide similar evidence for the rabbit antiserum directed against PME77 mAb.…”
supporting
confidence: 73%
See 2 more Smart Citations
“…Evidence has been presented elsewhere for the anti-Id specificity of the NZB and A/J mouse antisera prepared against F227 mAb (7). The data in Table 2 provide similar evidence for the rabbit antiserum directed against PME77 mAb.…”
supporting
confidence: 73%
“…Two of them were prepared in mice (NZB and A/J) against the F227 anti-DNA mAb. These sera detected different idiotopes on the F227 molecules (7). None of these idiotopes was present on the nine other 'purified anti-ds DNA mAb.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, the sharing of idiotypes amongst autoantibodies may offer clues to their origins. Earlier studies have demonstrated that there is much idiotype sharing amongst hybridoma-derived monoclonal anti-DNA antibody molecules found in the New Zealand black mice/New Zealand white mice (NZB/NZW) (19,20) and MRL lupus prone mice (21), and amongst human hybridomaderived anti-DNA autoantibodies (7). Further, anti-DNA autoantibody idiotype sharing has been shown amongst immunoglobulins in the serum of lupus patients (8).…”
Section: Discussionmentioning
confidence: 99%
“…This is significant in light of numerous studies which suggest that responses dominated by the expression of CRIs are particularly susceptible to idiotypic regulation. A majority of anti-DNA antibodies produced by lupusprone MRL-lprflpr and (New Zealand black x New Zealand white)F1 ([NZB x NZW]FI) mice express a CRI (16)(17)(18)(19)(20), as do the anti-DNA antibodies present in many humans with systemic lupus erythematosus (SLE) (21,22). CRIs have been identified on a high proportion of autoantibodies in the cerebrospinal fluid of patients with multiple sclerosis (23) and in the sera of patients with myasthenia gravis (24)(25)(26)(27).…”
Section: Idiotypic Regulation Of the Immune Systemmentioning
confidence: 99%